1997
DOI: 10.1016/s0375-9474(97)00265-0
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in direct neutron capture calculations due to nuclear structure models

Abstract: The prediction of cross sections for nuclei far off stability is crucial in the field of nuclear astrophysics. For spherical nuclei close to the dripline the statistical model (Hauser-Feshbach) approach is not applicable and direct contributions may dominate the cross sections. For neutron-rich, even-even Sn targets, we compare the resulting neutron capture cross sections when consistently taking the input for the direct capture calculations from three different microscopic models. The results underline the se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Furthermore, direct capture may play a role and is not included in rates we use. Rauscher et al [47] examined the direct-capture portion of the capture cross section of neutrons on nuclei and found that the direct-capture cross section varies by several orders of magnitude between the different theoretical models for 130 Sn [46]. While the inference that one can draw on rates at r-process temperatures from a comparison at 30 keV is limited, we note that [47], figure 9 shows the direct capture cross sections at low energy (30 keV) and the largest is about an order of magnitude smaller than the NON-SMOKER [26] rates at that same energy.…”
Section: Sn (N γ) At Late Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, direct capture may play a role and is not included in rates we use. Rauscher et al [47] examined the direct-capture portion of the capture cross section of neutrons on nuclei and found that the direct-capture cross section varies by several orders of magnitude between the different theoretical models for 130 Sn [46]. While the inference that one can draw on rates at r-process temperatures from a comparison at 30 keV is limited, we note that [47], figure 9 shows the direct capture cross sections at low energy (30 keV) and the largest is about an order of magnitude smaller than the NON-SMOKER [26] rates at that same energy.…”
Section: Sn (N γ) At Late Timesmentioning
confidence: 99%
“…Although the neutron capture cross section of 130 Sn is fairly consistent between the theoretical models that are depicted in figure 1, our understanding of the cross section is not complete. For example, Rauscher et al 1997 examined the direct-capture portion of the capture cross section of neutrons on nuclei and found that the direct-capture cross section varies by several orders of magnitude between the different theoretical models for 130 Sn [46]. In order to probe the influence of the uncertainties in the cross section, we introduce a scaling factor, χ, which modifies the 130 Sn neutron capture cross section …”
mentioning
confidence: 99%